Pancreatitis por hipercalcemia secundaria a un adenoma de paratiroides y la presencia de un carcinoma papilar tiroides asociado - Robles Cuadros, Juan Martín (2015)
Acute pancreatitis due to hypercalcemia secondary to primary hyperparathyroidism is a rare aetiology. We present a female patient with pancreatitis; with prior cholecystectomy, no alcohol usage or dyslipidemia. Laboratory studies showed, serum calcium 17.93 mg/dL and iPTH 441 pg/ml. Neck CT showed multinodular goiter and a parathyroid nodule. The patient underwent surgery after which serum Ca and PTH decreased. Biopsy showed follicular variant papillary thyroid carcinoma. This report discusses possible theories of association between parathyroid adenoma and hypercalcemic pancreatitis and describes the association with follicular variant papillary thyroid carcinoma, not previously described.